2020
DOI: 10.1002/adfm.202005033
|View full text |Cite
|
Sign up to set email alerts
|

Wool Can Be Cool: Water‐Actuating Woolen Knitwear for Both Hot and Cold

Abstract: As a second skin of the human body, clothing offers protection and aesthetic qualities. Because of the inability of materials to adapt to different weather conditions, different clothing is required for different seasons, namely, thin and open garments for summer, thick and closed ones for winter. Moreover, the body maintains its internal core temperature (37 °C) through sweating and shivering. Herein it is reported that woolen knitwear can provide not only warmth, but also a cooling sensation when a body swea… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
57
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 79 publications
(58 citation statements)
references
References 42 publications
1
57
0
Order By: Relevance
“…In Figure 4a, it has been noted that the fabricated samples have higher air permeability than the 3‐ply mask, uncovering the fact that there is a notable impact of highly porous knit structure (Table S1, Supporting Information) on as‐prepared WR thermophysiological comfort. Previous researches [ 27a ] further confirm fabric can significantly enhance air permeability with high pore size. Besides air permeability, the dry heat loss in terms of heat conduction has also been performed.…”
Section: Resultsmentioning
confidence: 84%
See 3 more Smart Citations
“…In Figure 4a, it has been noted that the fabricated samples have higher air permeability than the 3‐ply mask, uncovering the fact that there is a notable impact of highly porous knit structure (Table S1, Supporting Information) on as‐prepared WR thermophysiological comfort. Previous researches [ 27a ] further confirm fabric can significantly enhance air permeability with high pore size. Besides air permeability, the dry heat loss in terms of heat conduction has also been performed.…”
Section: Resultsmentioning
confidence: 84%
“…Recently, water‐actuating woolen knitwear has been introduced as cooling textiles. [ 27a ] Hence this water/sweat driven woolen knitwear may enhance thermal comfort performance of the respirators both in hot and cold. Besides, wool fiber has good biodegradability.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been reported that heat conductivity, infrared transmission and air permeability are three main methods of thermal management of textiles. 24 Therefore, the maximum of the infrared transmission IR max and efficiency of infrared transmission S IR expressing the infrared transmission performance were defined. These two indices are measured by the infrared detector array when a fabric covers the heat source but does not contact with the heat source on the moving slab.…”
Section: Apparatus Measurement Results and Analysismentioning
confidence: 99%